Reactive power control of grid-connected photovoltaic micro-inverter based on third-harmonic injection - Farah T. Noori; Turki K. Hassan (Institute of Advanced Engineering and Science, 2021)
This paper presents four interleaved flyback DC-DC converters. Each flyback converter contains a separate maximum power point tracker (MPPT). The MPP tracker is used to collect the maximum power value from photovoltaic panel by using (P&O) algorithm with an output of reference current. In latest years, the active third-harmonic injection circuit have received much interest, this technique contributed to getting a better quality of injection current into the utility grid and control the reactive power. For converting direct current to three-phase sinusoidal currents, a line-commutated current source inverter type (CSI) with filter is used. The developed micro-inverter of (1000 W) offers an expanded range of reactive power control with balanced three-phase output power and good efficiency 95.07%. The effectiveness of the suggested system is clarified through the MATLAB program simulation. The system proposed in this paper has proven its effectiveness in obtaining reactive power control, nearly sinusoidal three-phase output currents and it is compared with the traditional PV micro-inverter system. The comparison shows that the PV micro-inverter is best in more specification than the traditional PV system such as efficiency and total harmonic distortion (THD) and the system losses.